Thrombus Length Estimation on Delayed Gadolinium–Enhanced T1. Issue 3 (March 2016) - Yan, Shenqiang; Chen, Qingmeng; Xu, Mengjun; Sun, Jianzhong; Liebeskind, David S.; Lou, Min
Abstract : Background and Purpose—: Previous studies revealed a close relationship between thrombus length and recanalization rate after intravenous thrombolysis (IVT). As a novel approach, we prospectively adjusted the order of sequence acquisition to obtain delayed gadolinium–enhanced T1 (dGE-T1) and thereby assess thrombus length on dGE-T1 to evaluate its predictive value for recanalization after IVT. Methods—: We reviewed prospectively collected clinical and imaging data from acute ischemic stroke patients with middle cerebral artery occlusion who underwent multimodal magnetic resonance imaging before and 24 hours after IVT. Perfusion-weighted imaging was performed followed by conventional T1. We measured thrombus length on dGE-T1 and examined its association with middle cerebral artery recanalization. Results—: Of the included 74 patients, the median age was 66 years and 28 (37.8%) were women. Thrombus length was 8.18±4.56 mm on dGE-T1, which was an acceptable predictor for no recanalization (odds ratio, 1.196; 95% confidence interval, 1.015–1.409; P =0.033), with a receiver–operator characteristic of 0.732 (95% confidence interval, 0.619–0.845; P =0.001). The optimal cut-off point was identified at 6.77 mm, which yielded a sensitivity of 77.8%, a specificity of 57.9%, and an odds ratio of 4.81 (95% confidence interval, 1.742–13.292; P =0.002). Moreover, no one achieved recanalization after IVT when length of thrombus exceeded 14 mm on dGE-T1. Conclusions—: The dGE-T1, obtained by simply adjusting scanning order in multimodal magnetic resonance imaging protocol, is a useful tool for thrombus length estimation and middle cerebral artery recanalization prediction after IVT. Abstract : Supplemental Digital Content is available in the text.